Penggunaan Akronim dan Singkatan pada Acara Selebriti di Televisi - Anastasia Erna Rochiyati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2006)
Abstract Television as one form of audio visual medias represents human life. Using structural descriptive method and comparative study, this article tries to put forward a strong argument on the use of acronym and abbreviation at the infotainment broadcasted by private owned television company in Indonesia and try to study the result of the use of the acronym and abbreviation on homonym. The use of acronym and abbreviation in the infotainment can be classified into two: (1) the use based on the theory, and (2) the use which is not based on the theory. The use of acronym and abbreviation in those infotainments which is based on the theory affect positively on the development of homonym in Indonesian language in which the phenomena support constructively to the expansion of Indonesian vocabulary. Key words : acronym, abbreviation, impact, homonym.